The Impact of Parental Leave Policy on Child-Rearing and Employment Behavior: The Case of Germany - Chirkova, S (Walter de Gruyter GmbH, 2019)
Parental leave and child care are important instruments of family policies to improve work-family balance. This paper studies the impact of the substantial change in Germany’s parental leave system on maternal employment. The aim of the reform was to decrease birth-related maternal employment breaks by providing more generous parental benefits for a shorter period of time. Using the German Socio-Economic Panel data for 2002-2015, I exploited quasi-experimental variation in the benefits to estimate the impact of the reform. I incorporated the mother’s decision to substitute her care time with the public child care. To control for the availability of child care, I used spatial and temporal variation in the availability of childcare slots. Overall, I did not find significant changes in maternal employment during the first three years of motherhood after the reform implementation. Only for high-income mothers, the reform produced a significant decrease in the employment participation during the first year of leave and an increase in employment probability after the benefits expired. The empirical findings suggest that the restriction in the childcare availability became an important constraint for the employment effect of the reform. © The Author(s). 2019.